2017
DOI: 10.1097/inf.0000000000001359
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Acute Respiratory Infections in Infants

Abstract: In this cohort of infants, ARI incidence was 1.8 episodes per year per infant; 95% were upper respiratory tract infections. Viruses were identified in 63.3% episodes, and the most common viruses detected were rhinovirus, respiratory syncytial virus and parainfluenza virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
2
11
0
5
Order By: Relevance
“…(a) Multiplexing and the utility of identifying mixed infections. Multiplexing of molecular assays can facilitate identification of mixed viral infections (268)(269)(270). Coinfections are defined as the detection of more than one virus in a patient specimen.…”
Section: Molecular Panel Testing For Respiratory Viruses (I) Defininmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Multiplexing and the utility of identifying mixed infections. Multiplexing of molecular assays can facilitate identification of mixed viral infections (268)(269)(270). Coinfections are defined as the detection of more than one virus in a patient specimen.…”
Section: Molecular Panel Testing For Respiratory Viruses (I) Defininmentioning
confidence: 99%
“…For example, in Japan, a recent study found that 43.8% of patients who were diagnosed with a CoV infection were also infected with an additional virus (273). In another study, coinfections of two or more viruses were identified in approximately 18% of infants with an acute respiratory illness; RV was the most common coinfecting virus, but other viruses, such ADV, hMPV, and PIVs, were also codetected (270). Thus, the impact of mixed infection on patient outcomes is still under debate.…”
Section: Molecular Panel Testing For Respiratory Viruses (I) Defininmentioning
confidence: 99%
“…Bakteri adalah penyebab utama dan umum yang bertanggungjawab atas infeksi saluran pernapasan bawah, seperti Streptococcus pneumoniae. Ancaman ISPA juga dapat disebabkan oleh virus (syncytialvirus (RSV), human metapneumovirus (HMPV), coronavirus, enterovirus/ rhinovirus, virus influenza, virus parainfluenza, adenovirus) yang mudah bermutasi dan dapat menjadi ancaman serius yang menimbulkan epidemi maupun pandemi (Kumar et al, 2017;Naz et al, 2019). Terkadang pada beberapa kasus kejadian ISPA pada anak adalah koinfeksi virus atau bakteri atipikal yang dapat menimbulkan gejala yang lebih berat (El Baroudy et al, 2018).…”
Section: A Pendahuluanunclassified
“…The study was approved by the ethics committee of THSTI THS 1.8.1/(91) dated 13 April 2020. RNA samples from other respiratory virus infections were used from a study described previously (Kumar et al, 2017), which was a cohort of newborns who were followed for the first year of life, for each episode of acute respiratory infection. Nasopharyngeal aspirates were collected to identify the causative respiratory viruses using multiplex real-time PCR assay.…”
Section: Ethicsmentioning
confidence: 99%
“…To ascertain the selectivity of the assay, the stored RNA samples isolated from patients positive for other respiratory viruses, namely, parainfluenza virus (n = 1), influenza A virus (n = 2), human adenovirus (n = 1), rhinovirus (n = 4), human coronavirus OC43 (n = 1), and human respiratory syncytial virus (n = 1) were tested (Kumar et al, 2017).…”
Section: Assessment Of Cross-reactivitymentioning
confidence: 99%